Incidencia del carbón (ustilago scitaminea syd). En caña de azúcar (saccharum officinarum) en el Valle de CHICAMA – LA LIBERTAD - Honorio Aguilar, Ivar David (2013)
The present research work entitled incidence coal Ustilago scitaminea Syd in sugarcane (Saccharum officinarum) in the Chicama Valley - La Libertad, was conducted in the fields of agribusiness Cartavio and Casa Grande located in the Province of Ascope, Region La Libertad. Aiming determine the incidence of coal in sugarcane and to prevent infestation of cane fields and take appropriate control measures to prevent the spread of this disease. The plant material was composed of sugarcane cultivar varieties H-57, H-32, H-69 and H-61 of two to six months of age Casa Grande and Cartavio Enterprises. To determine the incidence of coal were used reports of evaluations in enterprises. It was concluded that the variety H-61 showed a higher incidence in all cane fields Enterprises Casa Grande with an average 352 whips / ha and Cartavio infested with an average of 150 whips / ha, currently the variety H-69 is behaving as the most susceptible to this disease after the H-61, according to the latest evaluations reports..